A combinatorial optimization formulation for the home away assignment problem (Publicaciones en Ciencias y Tecnología, 2013)
The sports scheduling problem has been center of attention in the Operational Research community due to their variety of models, and computational complexity of solutions (see for example Ribeiro (2010)). In a Round Robin tournament, the schedule is proposed by assigning a “home" or “away" labels to a preestablished itinerary, in a such way that the total distance traveled by the teams during the tournament is minimized. In terms of operation research, the problem is modeled as a binary quadratic programming problem with linear constraints. In Suzuka y cols. (2005) the problem is treated as a MIN-RES-CUT. In this work we study the structure of the home-away assignment problem, and propose a simplification of the combinatorial formulation. We solve exactly small instances of the problem with an exhaustive search, and also approximately solve larger instances with a random search.
Keywords: HA Assignment; Sports scheduling